Renoprotective role of tualang honey against high cholesterol diet induced acute kidney diseases in an animal model - Hamad Mohamed, Zenab B.; Hamad Alfarisi, Hamad Abdulsalam; Abdullah, Nor Zamzila; Harun, Norra; Muhammad, Siti Aeshah @ Naznin; Abdul Rahim, Roslina (2017)
The aim of this study is to determine the renoprotective effects of tualang honey against high cholesterol diet (HCD) induced acute and subacute kidney injuries in an animal model. Methodology: Ten female Sprague-Dawley rats were divided into two groups: the HCD group, fed with 12% cholesterol diet, and the HCD with tualang honey (HCD+TH) group, fed with HCD and daily dose of 1.4g/kg/day of tualang honey. Biochemical analysis of lipid and renal profiles were performed at 48 hours, 7 days, and 6 weeks. The animals were sacrificed after 6 weeks and the kidneys were harvested for histological examination. Results: The serum cholesterol and trigelyceride levels were significantly lower in the HCD+TH group as compared to the HCD group at 7 days with p values of 0.025 and 0.031 respectively. The HCD+TH group showed significantly lower serum creatinine level than the HCD group at 48 hours (p=0.018). The histological sections of the renal tissue of the HCD and HCD+TH groups both revealed segmental mesangial hypercellularity and mesangial matrix expansion of the glomeruli. Conclusion: Our study revealed that tualang honey exhibited some degree of renoprotective effect biochemically but not histologically in the rat models fed with high cholesterol diet.